Evaluation of Hydroxychloroquine Blood Concentrations and Effects in Childhood-Onset Systemic Lupus Erythematosus - Zahr, Noël; Urien, Saik; Funck-Brentano, Christian; Vantomme, Hélène; Garcelon, Nicolas; Melki, Isabelle; Boistault, Margaux; Boyer, Olivia; Bader-Meunier, Brigitte (Pharmaceuticals (Basel, Switzerland), 2021)
Background: Hydroxychloroquine (HCQ) is an antimalarial agent given to patients with systemic lupus erythematosus (SLE) as first-line therapy. It alleviates childhood-onset systemic lupus erythematosus cSLE skin and musculoskeletal disease, decreasing disease activity and flares. HCQ concentration–effect relationships in children remains unknown. This study aimed to investigate the pharmacokinetics of HCQ and possible concentration–effect relationships. Methods: HCQ blood concentrations and effects were obtained during clinical follow-up on different occasions. cSLE flares were defined using the SLE Disease Activity Index (SLEDAI); flare was denoted by a SLEDAI score > 6. Blood concentration was measured using high-performance liquid chromatography with fluorometric detection. Statistical analysis was performed using a nonlinear mixed-effect approach with the Monolix software. Results: A total of 168 blood samples were obtained from 55 pediatric patients. HCQ apparent blood clearance (CL/F) was dependent on patients’ bodyweight and platelet count. Patients with active cSLE had a lower mean blood HCQ concentration compared with inactive cSLE patients (536 ± 294 vs. 758 ± 490 ng/mL, p = 5 × 10−6). Among patients with HCQ blood concentration ≥750 ng/mL, 87.6% had inactive cSLE. Moreover, HCQ blood concentration was a significant predictor of disease status. Conclusion: We developed the first HCQ blood concentration–effect relationship for cSLE associated with active or non-active disease status. A prospective randomized study is necessary to confirm these results.